SYSTEMATIC LITERATURE REVIEW ON CLINICAL EFFICACY AND SAFETY OF ALOGLIPTIN IN COMPARISON WITH VILDAGLIPTIN, LINAGLIPTIN, SAXAGLIPTIN AND SITAGLIPTIN IN ADULT PATIENTS WITH TYPE 2 DIABETES MELLITUS - Georgii Rubenovich Khachatryan; Vladislav Sergeevich Dombrovskii (Фармакоэкономика, 2015)
Type 2 diabetes mellitus (T2DM) is one the socially important diseases in the Russian Federation (RF). Dipeptidyl peptidase-4 (DPP-4) inhibitors alogliptin, vildagliptin, linagliptin, saxagliptin and sitagliptin are registered in the RF and included in both russian and international modern guidelines on T2DM.Objective: to conduct a systematical review on clinical efficacy and safety of alogliptin in comparison with other DPP-4 inhibitors in adults with T2DM.Methods. We performed a search on efficacy and safety of alogliptin compared with vildagliptin, linagliptin, saxagliptin and sitagliptin in two electronic databases: Cochrane library and Medline up to June 15th, 2015. We also searched reference lists of the relevant articles. Methodological quality of five included articles was assessed.Results. Patients on alogliptin plus metformin achieved HbA1c <7% more frequently than those treated with saxagliptin plus metformin: odds ratio (OR) 6.41, 95% confidence interval (CI) (3.15; 11.98) vs. 2.17, 95% CI (1.56; 2.95). Indirect comparison of alogliptin vs. saxagliptin or sitagliptin is not appropriate due to the differences in age and prior cardiovascular diseases severity in patients with T2DM, included in randomized controlled trials (RCT) EXAMINE, SAVOR-TIMI 53 and TECOS.Conclusion. There were no differences in efficacy in T2DM between alogliptin and other DPP-4 inhibitors, apart from in patients on alogliptin plus metformin who achieved HbA1c <7% more frequently than those treated with saxagliptin plus metformin. Indirect comparison of safety of alogliptin vs. saxagliptin or sitagliptin is not appropriate due to the differences in population of T2DM patients included in relevant RCTs; indirect comparison of safety alogliptin vs. vildagliptin or linagliptin is impossible due to the absence of the evidence base.